Vidhi viveka of Maṇdana Miśra, understanding Vedic injunctions - Natarajan, Kanchana (Monumenta Indica series, 1995)
Critical study of the Vidhiviveka of Maṇḍanamiśra, classical treatise, presenting Mimamsa approach to the Vedic imperative sentence (vidhi).